PERBEDAAN VOLUME CAIRAN SULKUS GINGIVA ANTARA VEGETARIAN MURNI DAN VEGETARIAN TIDAK MURNI (Kajian pada Mahasiswa di Yogyakarta) - , DYAH AYU YOANITA, drg. Hendrawati, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Vegetarian is a person who only consume vegetable products and abstinence from meat. Generally, vegetarians are divided into two groups: pure vegetarian and impure vegetarian. A different nutrient intake in both groups may affect the periodontal condition that can be evaluated through the gingival crevicular fluid (GCF). This study aimed to determined the difference between the GCF volume of pure vegetarian and impure vegetarian (on college student in Yogyakarta). This observational analytic research involved 30 vegetarians who were divided into two groups: 15 people of pure vegetarians and 15 people of impure vegetarians who live in Yogyakarta city, 17-30 years old, and had been being a vegetarian at least 2 years. GCF was taken from each subject in both group with intrasulcular method. These method used filter paper in 10x1,5 mm size and 0,1 mm width which inserted to labial gingival sulcus of healthy gingiva of an anterior maxillary teeth. The paper was placed on the sulcus until it reached the bottom of the sulcus and left in there for 30 second. Filter paper was given 2 drops of 2% ninhydrin solution. The length of filter paper that stained by 2% ninhydrin solution measured on the 3 reference point and then the average was calculated. The results of length measurements multiplied by the width and thickness of filter paper and obtained a GCF volume (mm3). Then GCF volume data was analyzed using the Independent T-test. The results showed there was a highly significant differences (p <0.01) between the GCF volume of pure vegetarian and impure vegetarian. As the conclusion, there was a difference between the GCF volume of pure vegetarian and impure vegetarian, the GCF volume of a pure vegetarian was higher than impure vegetarian